Clinico-Pathologic Profile and Treatment Outcomes of Patients with Diffuse Large B Cell Lymphoma Based on Cell of Origin Classification - Mandloi, Sohan Singh (Indian J Hematol Blood Transfus, 2020)
Diffuse large B cell lymphoma (DLBCLs) constitute 40% of all non-Hodgkin lymphoma and it represent a heterogeneous group of neoplasms rather than a single clinicopathological entity. We analysed the outcomes and clinical features based on the cell of origin in a series of patients with DLBCL from our institute. Medical case records of all newly diagnosed DLBCL treated in our institute from January 2015 to July 2017 were analysed for this study. Cell of origin classification was based on immunohistochemistry using Hans algorithm. Kaplan–Meier curves were used to determine survival. Ninety-five patients were diagnosed to have DLBCL subtype. Immunophenotypic subtyping was available for 71 patients. The median age at diagnosis was 56 years with no difference between Germinal centre B cell (GCB) and non-Germinal centre B cell (non-GCB) subtypes. Approximately 44% of patients had extra-nodal disease, stomach being the commonest site. Forty percent of patients had stage III/IV disease. Bulky disease and extra-nodal presentation was predominantly seen with non-GCB subtype (46% vs 20% and 36% vs 29% respectively). Rituximab was used in 75% of the patients with DLBCL. The 2-year disease-free survival was 70% versus 53% (p = 0.38) in GCB versus non-GCB subtype. This is one of the few data on DLBCL patients reported from India which has described outcomes based on the cell of origin. The disease-free survival in our country appears to be superior in GCB subtype which needs to be confirmed in a larger subset of patients.